Visual evoked potentials – current concepts and future perspectives - Jančić, Jasna; Ivančević, Nikola; Nikolić, Blažo; Popović, Mirjana; Martinović, Žarko; Stevanović, Dejan; Grbić, Marina; Djurić, Vesna; Samardžić, Janko (Vojnosanitetski pregled, 2020)
No abstract for the review paper
Keywords: evoked potentials, visual; visual; multiple sclerosis; migraine disorders; epilepsy; optic nerve diseases; diagnosis.